Isolation and characterisation of metallothionein from the clam Ruditapes decussatus - Simes, D (2018)
Metallothioneins (MT) were obtained after purification from metal-exposed clams (Ruditapes decussatus) using gel-permeation and ion-exchange chromatography. Four cadmium-metallothioneins (CdMTs) were resolved by ion-exchange chromatography and they all had similar molecular weights, high cadmium content and an absorption spectra indicative of the presence of characteristic Cd-S aggregates. The NH2-terminal sequence suggests the presence of at least two class I clam MT isoforms. For the other two putative clam CdMTs isolated, the results of the amino acid determination were inconclusive. One was slightly contaminated and the other one had a blocked NH2-terminal. These clam metalothioneins contain glycine, which seems to be a common feature of molluscan MT family and exhibited more similarity to oysters than to mussels. Further investigation on the inducibility of these isoforms will be necessary if clams are to be used as biomarkers of metal exposure.